EFFECT OF ORGANIC SOURCE OF NUTRIENTS ON BLACK RICE (Oryza sativa L.) VARIETIES - B. SHEKHAR MAHANTA; VIKRAM SINGH; DHANANJAY TIWARI; NAREDDY HINDUJA; KRISHNA KUMARI AND ABHISHEK MAHAPATRA (The Bioscan, 2021)
The experiment was carried out during Kharif season 2019-20 at Crop Research Farm, SHIATS Model of Organic Farm (SMOF), Department of Agronomy, NAI, SHUATS, Prayagraj (U.P.) to study the “Effect of Organic Source of Nutrients on Black Rice (Oryza sativa L.) varieties”. Considering T 10 Kalabhat, Vermicompost (2.25 t/ha) and Jeevamrutha (500 l/ha)], performed significantly higher in plant height (163.02cm) and straw yield (26.57t/ha). Considering T 15 Manipuri black, Vermicompost (2.25 t/ha) and Jeevamrutha (500 l/ha) performed significantly higher in dry weight (191.48 g/hill), length of panicle (29.95cm), no. of grains/panicle (219.33), test weight (30.18 g), grain yield (5.61 t/ha), grain protein (15.60%) and also maximum B:C ratio (1:6.7). It can be concluded from the below research that application of Vermicompost (2.25 t/ha) and Jeevamrutha (500 l/ha) found to be enhancing productivity and economy of organic Manipuri black rice. Also it is a very good and sustainable cultivation practice.